(untitled) (Revista científica Olimpia, 2015)
In the empirical work presented below we have studied the reasons for the judges and referees Athletic decide to start, keep, change or stop using the DIP arbitration Technique 2 judges and 6 referees belonging to the municipal township panel Pilón. These judges and referees state that the main reasons for which were initiated in the arbitration activity were "achieve certain goals" and "fun"; among the reasons to continue refereeing point related to the enjoyment of the activity, with the list of group or with the technical knowledge of arbitration; the reasons that could lead them to change to another activity or leave the arbitration of athletics are related to the lack of support from the arbitration leaders, interference with school or work, and economic compensation. With this research is intended to contribute to the technological demands of INDER, linked to the need to apply studies of psychological preparation in the sports arbitration. Key words: professional motivation/ athletics/ arbitration board/ judges/ referees.